Co-occurrence of rhizobacteria with nitrogen fixation and/or 1-aminocyclopropane-1-carboxylate deamination abilities in the maize rhizosphere. Issue 5 (10th April 2020) - Renoud, Sébastien; Bouffaud, Marie-Lara; Dubost, Audrey; Prigent-Combaret, Claire; Legendre, Laurent; Moënne-Loccoz, Yvan; Muller, Daniel
ABSTRACT: The plant microbiota may differ depending on soil type, but these microbiota probably share the same functions necessary for holobiont fitness. Thus, we tested the hypothesis that phytostimulatory microbial functional groups are likely to co-occur in the rhizosphere, using groups corresponding to nitrogen fixation ( nifH ) and 1-aminocyclopropane-1-carboxylate deamination ( acdS ), i.e. two key modes of action in plant-beneficial rhizobacteria. The analysis of three maize fields in two consecutive years showed that quantitative PCR numbers of nifH and of acdS alleles differed according to field site, but a positive correlation was found overall when comparing nifH and acdS numbers. Metabarcoding analyses in the second year indicated that the diversity level of acdS but not nifH rhizobacteria in the rhizosphere differed across fields. Furthermore, between-class analysis showed that the three sites differed from one another based on nifH or acdS sequence data (or rrs data), and the bacterial genera contributing most to field differentiation were not the same for the three bacterial groups. However, co-inertia analysis indicated that the genetic structures of both functional groups and of the whole bacterial community were similar across the three fields. Therefore, results point to co-selection of rhizobacteria harboring nitrogen fixation and/or 1-aminocyclopropane-1-carboxylate deamination abilities. Abstract : The co-selection of different microbial functional groups reinforces the hypothesis that functions are more important than the taxonomic composition of the microbiota.